Synthesis of fluorine-modified polysilazanes via Si–H bond activation and their application as protective hydrophobic coatings. Issue 48 (30th November 2017) - Furtat, P.; Lenz-Leite, M.; Ionescu, E.; Machado, R. A. F.; Motz, G.
Abstract : A new method to synthesize fluorine-modified polysilazanes for processing of hydrophobic coatings with remarkable chemical stability for corrosion protection of metals. Abstract : A new route to synthesize fluorine-modified polysilazanes for coating applications with improved hydrophobicity and excellent chemical resistance was developed by the reaction of commercially available liquid oligosilazane Durazane® 1800 and fluorinated alcohol 2, 2, 2-trifluoroethanol (TFE) using tetra- n -butylammoniumfluoride (TBAF) as a selective catalyst to activate Si–H groups for simultaneous selective reactions with both N–H and O–H groups. Calcium borohydride (Ca(BH4 )2 ·2THF) was used as a reaction inhibitor, to terminate the reaction to obtain a solid, soluble fluorinated polysilazane, which is suitable for coating metal substrates via a simple dip-coating technique. The proposed reaction mechanisms and the resulting polymer structures confirm the attachment of the fluorinated groups on the polysilazane backbone; this was investigated by 1 H and 13 C NMR, FTIR, XPS, GPC, GC and elemental analysis. It was also demonstrated that the absence of catalysts leads only to the expected decomposition of the silazane by the alcohol. While the remaining silazane Si–H and Si–N bonds provide for an excellent adhesion of the coatings to the substrate, the CF3 groups decrease the surface energy leading to an increased contact angle of up to 15% and 40% to water and hexadecane, respectively, in comparison to fluorine-free polysilazane coatings. When tested as mold release coatings, the F-modified silazanes reduced the adhesion of a phenolic resin with an aluminum substrate from 12.7 to 2.8 MPa. Moreover, the chemical resistance of the fluorine-modified polysilazane based coatings in contact with acids and bases (HCl and KOH) is remarkably improved, offering great potential to protect metals from corrosion.